2022
DOI: 10.3390/ijerph19010522
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Nickel Oxide Nanoparticles Induces Acute and Chronic Inflammatory Responses in Rat Lungs and Perturbs the Lung Microbiome

Abstract: Nickel oxide nanoparticles (NiO NPs) are highly redox active nanoparticles. They can cause acute and chronic inflammation in rat lungs. Unlike the gut microbiome, the association between the lung microbiome’s role and pulmonary inflammatory response to inhaled nanoparticles remains largely unexplored. We aimed to explore the interaction between the lung microbiome and inflammatory responses in rats exposed to NiO NPs. Thirty female Wistar rats were randomly categorized into control and low- (50 cm2/rat), and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 53 publications
0
10
0
1
Order By: Relevance
“…Ni is required for both urease, and hydrogenase, two abundant and critical enzymes for the healthy existence of many micro-organisms [ 6 ]. Nickel oxide nanoparticles may also contribute to lung cancer with prolonged exposure via inhalation and have been reported to cause inflammation and oxidative tissue damage [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ni is required for both urease, and hydrogenase, two abundant and critical enzymes for the healthy existence of many micro-organisms [ 6 ]. Nickel oxide nanoparticles may also contribute to lung cancer with prolonged exposure via inhalation and have been reported to cause inflammation and oxidative tissue damage [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Фундаментальными исследованиями установлено, что наночастицы обладают высокой проникающей способностью и реактогенностью [6][7][8][9]. В бронхолегочной системе они запускают процессы воспаления [10], оксидативного стресса [11,12], фиброза [13], что определяет возможность их участия в патогенезе ПХОБЛ с формированием отдельного фенотипа. На данный момент недостаточно данных, свидетельствующих об ассоциации с определенными профессиональными этиологическими факторами основных значимых клинико-функциональных и клеточно-молекулярных показателей ХОБЛ.…”
Section: Methodsunclassified
“…Many in vitro and in vivo studies evaluating a multitude of health effects have been conducted with NiO NPs. Acute and chronic studies have shown that NiO NPs are associated with increased lung injury, inflammation, oxidative stress, apoptosis, and altered biochemical indices [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. A detailed analysis of these particular endpoints with considerations of various exposure routes, exposure durations, animal species, etc., is beyond the scope of this paper.…”
Section: Introductionmentioning
confidence: 99%